CREATIVITY IN FINE ART: THE ROLE OF CORE SELF-EVALUATION AND SOCIAL FEEDBACK - Raheem Okanlawon, Naibi (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Creativity is the driving force in every society's fine arts domain. Understanding what it means to be creative and the antecedents of creativity in the fine arts domain is fundamental to students' relationship with their lives and the art-making process. The present study examined personality and social variables (core self-evaluation and social feedback) as scarcely explored variables that could explain the variation in creativity among fine arts students. Participants in the study included one hundred and thirteen (n = 113) students enrolled in fine and applied art departments at tertiary institutions in River State, Nigeria. Self-report measures were used to obtain data. The data were subjected to a multiple linear regression analysis, which showed that CSE and social feedback significantly predicted creativity in fine arts. The result has implications for developing creativity in fine arts.